Progressividade efetiva das alíquotas do ITCD e o alcance da equidade entre os herdeiros e legatários no Distrito Federal - Faria, Solange Silva (2022)
Through the analysis of the ITCD collection data, the calculation bases, and corresponding rates, it was found that despite the existence of a small formal progressivity of the ITCD, there was no practical progressivity in the application of the tax. There is a prevailing rate of around 97% of total taxpayers in the amount of 4%. This demonstrates a big difference between what is in the legislation and what is actually done. The search for fiscal justice, the application of tax constitutional principles, in particular, the ability to pay, as everyone must contribute to public expenditures, due to their economic possibilities, is reflected in the creation of new ranges of calculation bases of the tax. Therefore, this research was directed to the study of the expected results and those achieved by the effective progressivity of the ITCD rates in the Federal District as a way of pointing out to the governments indications of the best use of their local public policies. With this, the literature review was based on the research of the origin of the tax, the role of ITCD in the Constitution, in the complementary laws, in the Ordinary laws, in the Federal District law, in the concept of progressivity, in the verification of the low efficiency of progressivity of the ITCD in the Federal District. The research was based on data from the year 2020, from the ITCD, from the records of tax transferors, number of acquirers, total value of the inheritance, percentage of the rate and calculation basis per acquirer, obtained from the systems of the Secretary of State for Economy. After the studies, it was concluded that the efficiency of the progressivity of the ITCD rates is low and other ITCD calculation base ranges were proposed, improving the progressivity of the rates without losing revenue, benefiting the taxpayer in the pursuit of social justice.